1989
DOI: 10.1016/0735-1097(89)90551-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of sympathetic nerve activity by single premature ventricular beats in humans

Abstract: This is the first systematic study of the effects of ventricular premature beats on sympathetic nerve activity in humans. Microneurographic techniques were used to record efferent sympathetic activity from the peroneal nerve, and an intracardiac electrode catheter was used to introduce ventricular premature beats after every 6 to 10 sinus heartbeats. Studies were performed in eight patients, aged 22 to 74 years (mean 57), undergoing cardiac electrophysiologic studies. Three patients did not have apparent heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
0
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(52 citation statements)
references
References 29 publications
4
47
0
1
Order By: Relevance
“…Furthermore, in these subjects the above-mentioned changes were followed by a transient diastolic BP increase and a concomitant transient suppression of spontaneous MSNA bursts. These findings are in line with the results of previous studies performed in both experimental animals 17 and humans, 1,18 in which a provoked PVC elicited, along with a diastolic BP reduction, a marked increase in cardiac, renal, and skeletal muscle sympathetic outflow, which was followed by a BP overshoot and a concomitant period of sympathetic silence. We can thus conclude that in healthy subjects, the sympathetic responses to provoked and unprovoked PVCs are qualitatively similar to each other, and thus, artificially induced PVCs represent a valid model for studying the hemodynamic and neural adjustments to spontaneously occurring arrhythmias of this type.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Furthermore, in these subjects the above-mentioned changes were followed by a transient diastolic BP increase and a concomitant transient suppression of spontaneous MSNA bursts. These findings are in line with the results of previous studies performed in both experimental animals 17 and humans, 1,18 in which a provoked PVC elicited, along with a diastolic BP reduction, a marked increase in cardiac, renal, and skeletal muscle sympathetic outflow, which was followed by a BP overshoot and a concomitant period of sympathetic silence. We can thus conclude that in healthy subjects, the sympathetic responses to provoked and unprovoked PVCs are qualitatively similar to each other, and thus, artificially induced PVCs represent a valid model for studying the hemodynamic and neural adjustments to spontaneously occurring arrhythmias of this type.…”
Section: Discussionsupporting
confidence: 82%
“…[12][13][14][15][16] In the present study, we investigated the behavior of the changes in MSNA, as directly quantified by microneurography, that follow spontaneous unprovoked PVCs in healthy subjects and in patients with EH or CHF. Because evidence in animals and man 1,17,18 suggests that the sympathetic changes after provoked PVCs are related to (1) the blood pressure (BP) changes induced by PVCs, (2) their degree of prematurity (expressed by the coupling interval time), and (3) the level of the resting sympathetic tone, we further investigated in the 3 groups the relationships between the MSNA adjustments to spontaneous PVCs and the above-mentioned variables. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Burst area was used because ventricular pacing often produces broad arterial pressure oscillations that provoke broad bursts of sympathetic activity. Under these conditions, burst amplitude alone does not correlate well with burst area 4 and does not account for the prolonged activation of sympathetic nerve traffic associated with periods of protracted hypotension.…”
Section: Sympathetic Nerve Recordingsmentioning
confidence: 99%
“…In an earlier study by Huikuri et al, an increase in sinus rate was demonstrated during induced VT. 41 They suggested that both vagal withdrawal and sympathetic activation may play a role in the increase in sinus rate during VT. Other experimental and clinical studies have shown an increase in sympathetic nerve activity during programmed ventricular stimulation 42 and induced VT, 43 and even in the presence of PVC. 44 In the present study, increased vagal tone and decreased sympathetic tone were demonstrated after the successful ablation.…”
Section: Effect Of Rf-ca On Hrvmentioning
confidence: 68%